Primary splenic leiomyosarcoma as an exceptionally rare cause of ruptured splenomegaly - A case report and review of primary splenic sarcomas - Benjamin Livingston Farah; Yen Min Madeline Chee; Siok Siong Ching; Chien Sheng Tan (Elsevier, 2020)
Primary splenic leiomyosarcoma has not been included in the recent WHO classification of tumours of spleen. Primary splenic leiomyosarcomas are exceedingly rare. Most cases of splenic leiomyosarcomas are described in animals. These tumours are very rarely encountered in human, usually in old patients, and frequently presented with constitutional symptoms or in autopsy setting. Surgical pathologists should be aware of their existence. We present a case of a primary splenic leiomyosarcoma and a comprehensive review of other rarely encountered splenic sarcomas.